Development of a protein-based system for transient epigenetic repression of immune checkpoint molecule and enhancement of antitumour activity of natural killer cells - Teratake, Yoichi; Takashina, Tomoki; Iijima, Kenta; Sakuma, Tetsushi; Yamamoto, Takashi; Ishizaka, Yukihito (British journal of cancer, 2020)
Background Immune checkpoint blockade (ICB) therapy improved the prognosis of cancer patients, but general administration of ICBs occasionally induces side effects that include immune-related adverse events and tumour hyper-progression. Here, we established a protein-based system, by which endogenous expression of IC molecule in natural killer (NK) cells was transiently repressed on enhancement of their antitumour activity. Methods A protein-based genome modulator (GM) system is composed of a transcription activator-like effector (TALE), DNA methyltransferase and a newly identified potent cell-penetrating peptide with nuclear-trafficking property named NTP. TALE was designed to target the promoter region of the programmed cell death-1 ( PD-1 ) gene. After culturing human NK cells in the presence of NTP-GM protein, we examined endogenous PD-1 expression and antitumour activity of the treated cells. Results NTP-GM protein efficiently downregulated PD-1 expression in NK cells with increased CpG DNA methylation in the promoter region. The antitumour activity of the treated NK cells was enhanced, and repeated intraperitoneal administrations of the treated NK cells attenuated tumour growth of programmed death-ligand 1-positive tumour cells in vivo. Conclusions Because the incorporated NTP-GM protein was quickly degraded and negligible in the administered NK cells, the NTP-GM system could be an alternative option of an ICB without side effects.